A Process-Based Approach to Psychological Diagnosis and Treatment:The Conceptual and Treatment Utility of an Extended Evolutionary Meta Model - Hayes, Steven C. (Clin Psychol Rev, 2020)
For half a century, the dominant paradigm in psychotherapy research has been to develop syndrome-specific treatment protocols for hypothesized but unproved latent disease entities, as defined by psychiatric nosological systems. While this approach provided a common language for mental health problems, it failed to achieve its ultimate goal of conceptual and treatment utility. Process-based therapy (PBT) offers an alternative approach to understanding and treating psychological problems, and promoting human prosperity. PBT targets empirically established biopsychosocial processes of change that researchers have shown are functionally important to long terms goals and outcomes. By building on concepts of known clinical utility, and organizing them into coherent theoretical models, an idiographic, functional-analytic approach to diagnosis is within our grasp. We argue that a multi-dimensional, multi-level extended evolutionary meta-model (EEMM) provides consilience and a common language for process-based diagnosis. The EEMM applies the evolutionary concepts of context-appropriate variation, selection, and retention to key biopsychosocial dimensions and levels related to human suffering, problems, and positive functioning. The EEMM is a meta-model of diagnostic and intervention approaches that can accommodate any set of evidence-based change processes, regardless of the specific therapy orientation. In a preliminary way, it offers an idiographic, functional analytic, and clinically useful alternative to contemporary psychiatric nosological systems.